Pengaruh Penerapan Sistem Digitalisasi terhadap Kinerja Karyawan Di Daima Hotel Padang - Nabila salsabila; Feriantano Sundang Pranata; Era Gumala Astia (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This research is motivated by the growing use of digital systems in the hospitality sector, a shift that compels employees to adjust to technology-driven work routines. While the relationship between digitalization and employee performance has been examined in numerous prior studies, findings remain mixed, and most of that work concentrates on banking and telecommunications, leaving hospitality comparatively underexplored. Accordingly, this study seeks to measure how far the adoption of a digital system shapes employee performance at Hotel Daima Padang. A quantitative, descriptive-associative-causal design was applied. Because all 35 employees who operate the Property Management System (PMS) directly in their daily duties were treated as both population and sample, saturation sampling was used. Primary data were gathered through an online Likert-scale questionnaire and processed with simple linear regression. Results show that both employee performance and system digitalization fall into the good category, with mean scores of 3.51 and 3.46 respectively. The t-test demonstrated a statistically significant, positive influence of digitalization on performance (calculated t = 19.083 > critical t = 2.035; p < 0.001), while a coefficient of determination of 91.7% indicates that nearly all variation in employee performance is accounted for by the digital system, with the remaining 8.3% attributable to factors beyond this study's scope. These findings are expected to enrich the human resource management literature within the hospitality sector, particularly concerning technology use in hotel operations.